Cleopatra in space. Book five, Fallen empires - Maihack, Mike (New York : Graphix, 2019)
Cleo goes into hiding after a mysterious death at Yasiro Academy, and she and her friends set out to uncover the spy who must be working within the school's ranks. Meanwhile, Xaius Octavian continues his assault on the galaxy as his complicated origin story--and how he went from being Cleo's best friend to a ruthless dictator--is revealed. In the end, a space battle and dramatic confrontation between Cleo and Octavian will change both of their lives forever.
3.8
3-6
GN370L
Keywords: Cleopatra, -- Queen of Egypt, -- -30 B.C. -- Comic books, strips, etc. -- Fiction; Schools -- Comic books, strips, etc. -- Fiction; Time travel -- Comic books, strips, etc. -- Fiction; Science fiction comic books, strips, etc; Cleopatra, -- Queen of Egypt, -- -30 B.C. -- Juvenile fiction; Schools -- Juvenile fiction; Time travel -- Juvenile fiction; Science fiction; Cartoons and comics; Science fiction comics; Graphic novels; Graphic novels